Errors in Shaping the Ergonomics of the Elderly-Interface Interaction - Kamil WRÓBEL (Communications of International Proceedings, 2021)
Current observations of researchers on the ergonomics of human-computer interfaces incline for the research on management and optimization of ergonomic requirements with respect to the elderly preferences, for which the identification of errors and their origins can be very supportive. The purpose of paper is to present the pilot study results for the influence of computer mice features and the elderly preferences on personalized shaping the interaction ergonomics, with regard to the errors. In the research included the ethnographic analysis, identification and summation of errors, as well as the deviations and mean values for the results.  It was demonstrated in the research, that the properties of mice were of greater importance than differentiation in the elderly preferences, when it comes to the shaping of ergonomics interaction. Logical principles of profiling the elderly-interface interaction are covered with the results and conclusions. Thanks to the application of logical principles on the basis of the evaluated errors, one may obtain the personalized device project  consistent with the perception of a human being.
Keywords: Evaluation of ergonomics; the elderly; management of human-computer interaction; computer control devices.